2020
DOI: 10.3390/jcm9092780
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antibodies to SARS-CoV-2 in Italian Adults and Associated Risk Factors

Abstract: We aimed to assess the prevalence of and factors associated with anti- severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) positivity in a large population of adult volunteers from five administrative departments of the Liguria and Lombardia regions. A total of 3609 individuals were included in this analysis. Participants were tested for anti-SARS-CoV-2 antibodies [Immunoglobulin G (IgG) and M (IgM) class antibodies] at three private laboratories (Istituto Diganostico Varelli, Medical Center, and Casa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
88
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(108 citation statements)
references
References 37 publications
15
88
5
Order By: Relevance
“…The rate of seroprevalence reported in Corsica is closer to the rate reported by a similar study in a French region with a low proportion of COVID-19 cases during the epidemic period (3%) than those reported in two regions with the highest rates (9-10%) [22]. The observed seroprevalence in our population is in line with ELISA-S values reported in Spain, New York City, and in different subcohorts of Wuhan [23], the United States [24], and China [25], but lower than values reported in heavily affected areas such as Switzerland [26], northern Italy [27], and the urban areas around Madrid [28].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The rate of seroprevalence reported in Corsica is closer to the rate reported by a similar study in a French region with a low proportion of COVID-19 cases during the epidemic period (3%) than those reported in two regions with the highest rates (9-10%) [22]. The observed seroprevalence in our population is in line with ELISA-S values reported in Spain, New York City, and in different subcohorts of Wuhan [23], the United States [24], and China [25], but lower than values reported in heavily affected areas such as Switzerland [26], northern Italy [27], and the urban areas around Madrid [28].…”
Section: Discussionsupporting
confidence: 86%
“…In France, the SARS-CoV-2 epidemic period ranged from 2020w09 (24)(25)(26)(27)(28)(29) to 2020w19 (4-10 May), with an epidemic peak at 2020w13 (23)(24)(25)(26)(27)(28)(29) and a positivity rate of up to 30%, affecting mostly the Paris and northeastern regions of the country [9]. To respond to the epidemic, on 17 March (2020w12), France ordered all non-essential retailers and services to be closed, and the general population to remain confined.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary results from the Corona Immunitas study in a representative sample of the Ticino population suggest that 11% of adults between 20 and 64 years of age developed detectable antibodies against SARS-CoV-2 ( https://www.usi.ch/it/feeds/14492 ). Other previous serological studies in the Geneva Canton, as well as in France, Italy and Spain showed similar results [27] , [28] , [29] , [30] . Infection rates and community transmission in the general population might be slightly higher compared to the overall seroprevalence in HCWs, and the seropositivity among HCWs at high risk of exposure was only 3% higher than in the local general population.…”
Section: Discussionsupporting
confidence: 83%
“…Another seroprevalence study in Northern Italy locations found that seroprevalence was 4.5 times larger in nursing home residents compared with non-institutionalised people. 35 While these data may not necessarily be representative of Italy as a whole, they are congruent with the very high fatalities in particular areas of Lombardy in the first wave. 36 …”
Section: Precision Shielding Placed Into Contextmentioning
confidence: 88%